2002
DOI: 10.1091/mbc.e01-12-0149
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Pulses and Metabolic Oscillations Guide Yeast Colony Development

Abstract: On solid substrate, growing yeast colonies alternately acidify and alkalinize the medium. Using morphological, cytochemical, genetic, and DNA microarray approaches, we characterized six temporal steps in the "acid-to-alkali" colony transition. This transition is connected with the production of volatile ammonia acting as starvation signal between colonies. We present evidence that the three membrane proteins Ato1p, Ato2p, and Ato3p, members of the YaaH family, are involved in ammonia production in Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(191 citation statements)
references
References 30 publications
9
182
0
Order By: Relevance
“…earlier than in the wt strain), but its overall level of expression from the 26th h onwards was lower than in the wt. Most of the above data indicate that pdr5/snq2 cultures activate a metabolism to some extent similar to that described previously on glycerol medium [32].…”
Section: The Absence Of Pdr5p and Snq2p But Not Of Yor1p Influencessupporting
confidence: 85%
“…earlier than in the wt strain), but its overall level of expression from the 26th h onwards was lower than in the wt. Most of the above data indicate that pdr5/snq2 cultures activate a metabolism to some extent similar to that described previously on glycerol medium [32].…”
Section: The Absence Of Pdr5p and Snq2p But Not Of Yor1p Influencessupporting
confidence: 85%
“…3 and 4). These defects can be related to the fact that sok2 colonies do not produce a significant amount of volatile ammonia, the proposed signal of nutrient exhaustion, of transient growth arrest, and of changes allowing cells to economize their metabolism (1,3). The process of ammonia production can be influenced at least at three steps: (i) formation of free intracellular ammonium, (ii) export of ammonium out of the cells, and (iii) conversion of NH 4 ϩ to NH 3 and its volatilization.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings revealed that the acid-to-alkali colony transition is connected with significant changes in gene expression, indicating a parallel decrease in stress factors and mitochondrial respiratory functions, a switch from the mitochondrial citrate cycle to the methylglyoxylate cycle, enabling more economical exploitation of nutrients, and mobilization of cell reserves by means of ␤-oxidation of fatty acids in peroxisomes. Additionally, we observed significant changes in the expression of genes coding for various membrane proteins/transporters including those that may be important for ammonia production (Ato transporters) (3). Monitoring the behavior of colonies of strains defective in several particular genes allowed us to identify the gene encoding transcription factor Sok2p as a regulator possibly affecting long term colony development.…”
mentioning
confidence: 99%
“…Remarkably seven subunits of the F 0 F 1 -ATPase were phosphorylated, suggesting that this central machinery for cellular ATP production is a frequent target for covalent modification. Among the phosphorylated transport proteins, Ato2, Ato3, and Ady2 belong to the GPR1/FUN34/yaaH family and are potential permeases for acetate and ammonium (66,67). For Ato2, Ato3, and Yat1 of the lipid metabolism group, a role in mitochondrial retrograde signaling was reported (6).…”
Section: Identification Of Phosphorylation Sites Of Yeastmentioning
confidence: 99%